Energy Requirement Evaluation of Spray Distillation Technology as Green Alternative of Bioethanol Downstream Processing: Evaluasi Kebutuhan Energi dari Teknologi Distilasi Spray sebagai Alternatif Hijau Proses Hilirisasi Bioetanol - Kartawiria, Irvan; Widiputri, Diah Indriani (Jurnal Rekayasa Bahan Alam dan Energi Berkelanjutan, 2023)
Bioethanol downstream processing is consuming 40-60% of total energy requirement in production of bioethanol as fuel, with highest consumption being the evaporation and distillation process. One of the technologies currently in development stage is spray distillation. In spray distillation, ethanol-water mixture feed is dispersed as micro droplets into a heated column at 40oC, while counter current air is flown upward to collect the vapor and discharged into condensation column. Since the spray distillation principles has been tested in controlled laboratory scale, this research objective is to evaluate the energy requirement for such process and comparison to conventional distillation. Testing was conducted on 20 L batch stainless steel column distillation and spray distillation of the same capacity. The ethanol concentration in feed was set to 15%-v to simulate fermentation broth, and operating parameters were sets to obtain 80%-v product. Batch distillation was heated using LPG gas and calculation shows that heat requirement 3.34 MJ/L pure ethanol equivalent. Alternatively, spray distillation running with feed rate of 5.05 ml/s at 40oC only requires 2.2-2.6 MJ/L pure ethanol equivalent. The study shows potential of spray distillation technology in reducing the energy requirement in downstream processing of bioethanol to 62-79% of conventional distillation.